Prediction of injuries, traumas and musculoskeletal pain in elite Olympic and Paralympic volleyball players - Anna Zwierzchowska; Eliza Gaweł; Miguel-Angel Gómez; Aleksandra Żebrowska (Scientific Reports, 2023)
Abstract The study aimed to identify the prevalence and location of injuries, traumas, and musculoskeletal complaints in Paralympic and Olympic volleyball players with different impairments and initial playing positions (sitting/standing); and to identify the predictors of the abovementioned variables using a multivariate CRT model. Seventy-five elite volleyball players from seven countries took part in the study. They were divided into three study groups: (SG1)—lateral amputee Paralympic volleyball players, (SG2)—able-bodied Paralympic volleyball players, (SG3)—able-bodied Olympic volleyball players. The prevalence and location of the analyzed variables were assessed with surveys quessionaires, while game-related statistics was interpreted based on the CRT analysis. Regardless of the impairment or initial playing position, both the humeral and knee joints were found to be the most frequent locations of musculoskeletal pain and/or injuries in all studied groups, followed by LBP. Players from SG1 and SG3 were characterized by an almost identical prevalence of reported musculoskeletal pain and injuries, what was not noted in SG2. Extrinsic compensatory mechanism (playing position) may be a crucial variable for prediction of musculoskeletal pain and injuries in volleyball players. Lower limb amputation seems to impact the prevalence of musculoskeletal complaints. Training volume may predict the prevalence of LBP.